(18)F-FDG PET/CT Is an Immediate Imaging Biomarker of Treatment Success After Liver Metastasis Ablation - Cornelis, Francois (J Nucl Med, 2016)
The rationale of this study was to examine whether (18)F-FDG PET/CT and contrast-enhanced CT performed immediately after percutaneous ablation of liver metastases are predictors of local treatment failure at 1 y. METHODS: This Health Insurance Portability and Accountability Act–compliant, Institutional Review Board–approved retrospective study reviewed 25 PET/CT-guided thermal ablations performed from September 2011 to March 2013 on 21 patients (11 women and 10 men; mean age, 56.8 y; range, 35–79 y) for the treatment of liver metastases (colorectal, n = 23; breast, n = 1; and sarcoma, n = 1). One to 3 tumors (mean size, 2.3 cm; range, 0.7–4.6 cm; mean SUV(max), 22.7; range, 9.5–77.1) were ablated using radiofrequency (n = 16) or microwave (n = 9) energy in a single session. Immediate-postablation enhanced CT and PET/CT scans were qualitatively evaluated by 2 reviewers independently, and the results were compared with clinical and imaging outcome at 1 y. The PET/CT scans were also analyzed to determine tissue radioactivity concentration (TRC) from 3-dimensional regions of interest in the ablation zone, the margin, and the surrounding normal liver to calculate a TRC ratio, which was then compared with outcome at 1 y. Receiver operating characteristics (ROC) were used, and the maximal-accuracy threshold in predicting recurrence was calculated. RESULTS: Eleven (44%) of the 25 tumors recurred within 1 y. Enhanced CT did not significantly correlate with recurrence (P = 0.288). Accuracy was 64% (16/25), and the area under the ROC curve was 0.601 (95% confidence interval [95% CI], 0.387–0.789). The accuracy of the qualitative analysis of (18)F-FDG PET was 92% (23/25) (P < 0.001), and the area under the ROC curve was 0.929 (95% CI, 0.740–0.990). The mean TRC ratio was 40.6 in the recurrence group (SD, 9.2; range, 29.3–53.9) and 15.9 in the group without recurrence (SD, 7.3; range, 3–27.3). A TRC ratio of 28.3 predicted recurrence at 1 y with 100% accuracy (25/25) (P < 0.001), and the area under the ROC curve was 1 (95% CI, 0.863–1). CONCLUSION: Immediate PET/CT accurately predicts the success of liver metastasis ablation at 1 y and is superior to immediate enhanced CT.